2019
DOI: 10.1111/acel.12931
|View full text |Cite
|
Sign up to set email alerts
|

Aged‐senescent cells contribute to impaired heart regeneration

Abstract: Aging leads to increased cellular senescence and is associated with decreased potency of tissue‐specific stem/progenitor cells. Here, we have done an extensive analysis of cardiac progenitor cells (CPCs) isolated from human subjects with cardiovascular disease, aged 32–86 years. In aged subjects (>70 years old), over half of CPCs are senescent (p16INK4A, SA‐β‐gal, DNA damage γH2AX, telomere length, senescence‐associated secretory phenotype [SASP]), unable to replicate, differentiate, regenerate or restore card… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(156 citation statements)
references
References 47 publications
5
126
1
1
Order By: Relevance
“…The secretions from senescent cells lead to a senescence-associated secretory phenotype (SASP), which might contribute to aging-associated tissue dysfunction or the development of a cancerous niche in old tissue (Coppe et al, 2010;Castro-Vega et al, 2015;Buhl et al, 2019;Lopes-Paciencia et al, 2019). A recent study showed that the transplantation of senescent cells into mice leads to the early onset of aging-related phenotypes (Xu et al, 2017(Xu et al, , 2018, which supports the current hypothesis that senescence can be a driver of aging (Krtolica et al, 2001;Sturmlechner et al, 2017;Lewis-McDougall et al, 2019).…”
Section: Introductionsupporting
confidence: 56%
“…The secretions from senescent cells lead to a senescence-associated secretory phenotype (SASP), which might contribute to aging-associated tissue dysfunction or the development of a cancerous niche in old tissue (Coppe et al, 2010;Castro-Vega et al, 2015;Buhl et al, 2019;Lopes-Paciencia et al, 2019). A recent study showed that the transplantation of senescent cells into mice leads to the early onset of aging-related phenotypes (Xu et al, 2017(Xu et al, , 2018, which supports the current hypothesis that senescence can be a driver of aging (Krtolica et al, 2001;Sturmlechner et al, 2017;Lewis-McDougall et al, 2019).…”
Section: Introductionsupporting
confidence: 56%
“…In subsequent studies, D+Q has been shown to elicit beneficial effects on cardiac regenerative capacity, frailty, osteoporosis, muscle weakness and endurance, and to extend lifespan [36][37][38]. In studies in human, D+Q alleviated physical dysfunction in patients with idiopathic pulmonary fibrosis and in subjects with diabetic kidney disease, D+Q reduced senescence cell burden in the adipose tissue [39,40].…”
Section: Anti-aging Therapiesmentioning
confidence: 99%
“…Thus, the leaking mtDNA activates caspase-1 and promotes the secretion of IL-1β and IL-18 in macrophages. In the aged heart, the increased senescent cells modulate inflammation through secreting chemokine and cytokines, such as IL-1β, IL-6, and IL-8, termed the senescence-associated secretory phenotype (SASP) [19,20]. The cyclic GMP-AMP synthase (cGAS) is a stimulator of the interferon genes (STING).…”
Section: Inflammation In Cardiacmentioning
confidence: 99%